The Maputo Corridor : politics and pragmatic development in Southern Africa - Pyne-Mercier, Lee David (Department of Political Studies, 2016)
The Maputo Corridor is the most significant development project undertaken by the South African government since 1994. The Corridor is an extremely complex project, bringing together a variety of actors from South Africa, Mozambique, and beyond. The project includes the rehabilitation and upgrading of major transport and communications infrastructure between Witbank and Maputo, institutional reform to expedite border-crossing, and incentives for labour-intensive investment in the areas adjacent to the Corridor. The Maputo Corridor is also the first build-operate- transfer highway in the region. The Maputo Corridor is a valid and fascinating subject for political inquiry because it provides insight into the new South African government's priorities and ideological stance. Research on the Corridor also contributes to our understanding of political power structures in the region. The primary goal of this dissertation was to come to an understanding of why and how the Maputo Corridor developed. Research was designed to test popular hypotheses from the South African media. These hypotheses were (1) that the Corridor was designed to isolate Gauteng from potential transport-based blackmail by the IFP and (2) that the Corridor was sponsored and directed by the leaders of Mpumalanga Province. This dissertation is composed of four main sections. First, the historical context of the Corridor starting in the 19th century is investigated. Repetitive historical themes with relevance for the present are identified. Second, the leaders and managers of the corridor project are pinpointed. Third, strategic motivations for the corridor in the current political environment are studied. The fourth part consists of an investigation of the means used to implement the Corridor. Several sources of information were used. These sources included indepth interviews with the Corridor's stakeholders, primary documentation, and secondary published sources.